Influence of adaptability of Serious Games on learning outcomes and the application of knowledge and skills in professional training - Pistono, Alvaro Marcos Antonio de Araujo (2023)
Serious Games have been studied in various fields and contexts, including academic education and professional training. While Serious Games have been utilised in professional training for over two decades, there is a need for more evidence-based approaches to assessing their effectiveness in promoting learning. Thus, this investigation aims to address the efficiency of utilising Serious Games in professional training through e-learning, with the primary motivation of improving the teachinglearning process through the use of adaptive Serious Games. Using the Design Science Research – DSR methodology, a Framework for Adaptive Serious Games – F4ASG has been developed to adapt its elements to achieve desired learning and engagement outcomes. This framework draws from the literature, expert and user experiences of Serious Games in professional training, treating learning outcomes and forms of adaptation as essential characteristics for developing or evaluating Serious Games. The adaptation in the F4ASG aims to direct learners towards better learning outcomes and increased engagement. The investigation began with a systematic literature review to answer research questions and analyse existing frameworks of Serious Games. The theoretical basis formed the initial proposal of the framework, which was evaluated through triangulation with focus groups and expert interviews, resulting in its second version. The second version of the framework was used to develop and evaluate a Serious Game, providing new insights and application suggestions. The developed Serious Game was utilised in an experiment, providing a third evaluation of the framework. The experimental evaluation and application suggestions were incorporated into the F4ASG, resulting in its third and final version. Overall, this investigation contributes to developing evidence-based approaches for the effective use of Serious Games in professional training. The F4ASG provides a guide for developing and evaluating Serious Games that adapt to promote desirable learning and engagement outcomes.